PENGGUNAAN ISTILAH BAHASA INGGRIS DI BAGIAN FRONT OFFICE : STUDI KASUS DI HOTEL CROWNE PLAZA SEMARANG - Cindy Citya Dima (LITE: Jurnal Bahasa, Sastra, dan Budaya, 2017)
Hotel terminology has long been used in English language since the first establishment of Convent Garden hotel in 1774 in Westminfer, London.The following hotel named City Hotel was then found in1794 located in New York City.Hotels were growing rapidly in Europe as well as in America during the 19th and 20th century. Meanwhile in Indonesia, the first hotel with an international standard known as Hotel Indonesia was established on 5 August 1962. However, hotels today mainly recruit new qualified employees with hotel management backgrounds. The graduates of Hotel Management department are provided with the good skills in practicing the hotel terminology during the study. The hotel terminology itself is particularly employed the most in job interviews. This article shows the easiest way of learning by heart and putting into practice the hotel terminology by defining each term in alphabetical order. The hotel terms apply the most to the Front Office department leading to other departments such as Housekeeping, Food & Beverage Services, Food & Beverage Products, Accounting, Sales & Marketing and Safety & Risk. In conclusion, the Front Office department is the main department carrying abundant knowledge about the hotel terminology.Keywords : front office, hotel division ,hospitality language , hotel terminology